Georgia : Agricultural and Rural Enterprise Development - World Bank (Washington, DC, 2013)
The report is structured as follows. Section one examines the contribution of the rural economy to the national economy, the structure of the farm and non-farm sectors and their relative importance. Section two describes policies and constraints affecting the wider rural economy including, reforms in macro-economic management, recent external influences and financial services before discussing those which relate specifically to agriculture including, agricultural trade policy, land reform, agricultural machinery services , irrigation and drainage, seeds, sanitary and phytosanitary control and veterinary services, marketing and advisory services. Section three assesses the outcomes of these policies on the structure and performance of the rural economy. Section four describes the extent to which policy makers should prioritize the farm and non-farm sectors in rural areas and then presents recommendations for reform. While it is recognized that rural infrastructure (roads, potable water, and energy) and rural social services have a major impact on the rural economy, the report does not attempt to address these issues in detail. Rural Infrastructure issues are examined in 'rural infrastructure in Georgia, improving service delivery' (World Bank, 2006) and key findings of this report are summarized at the end of section two.